Evaluating Usability of a Website-Based Learning Platform for Basic Programming Using the SUS Method - Alifya NFH; Ayu Tri Wardani (Jurusan Teknik Informatika dan Komputer, 2025)
This study aims to evaluate the usability of a website-based learning platform for basic programming using the System Usability Scale (SUS) method. The platform is designed to help students understand fundamental concepts through interactive features such as structured materials, video explanations, practice questions, and visual illustrations of code execution. The usability evaluation employed a descriptive quantitative approach involving 28 respondents who used the platform and completed the SUS questionnaire. The analysis results show that the platform achieved an average SUS score of 75, which falls into the “Good” and “Acceptable” categories. However, there was notable score variation, with a minimum of 42.5 and a maximum of 100, and a standard deviation of 13.35. This suggests that while most users were satisfied, a minority faced challenges such as feature complexity and the need for additional guidance. Recommendations for improvement include simplifying navigation, enhancing interface consistency, and providing interactive tutorials to better support users.